How Colored Passwords Can Improve the Usability of Coercion-resistant Internet Voting Systems - de Sá, Matheus Leite; Araujo, Roberto; Sobrinho, Alberto Lima; Silva Neto, André; Maximino, Gabriela S.; Traoré, Jacques (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Coercion is an inherent problem of any Internet election. Because there is no voting booth to protect the voter while she is voting, a coercer can easily influence them to choose his candidates. In order to mitigate these problems, coercion-resistant voting protocols employ the idea of voting credentials. Voters use their legitimate credentials to authorize the corresponding votes that will appear in the final tally. When voters are under coercion, they use fake credentials to deceive adversaries about their true vote intention. Credentials, however, are usually composed of large numeric values and have low usability to be used in real world elections. As a result, voters can incorrectly manage them and thus undermine the coercion-resistance. In this context, this work proposes a novel method to improve the credential usability called colored passwords. The new method is based on a known password technique and abstracts the numeric value of the credential. To show the application of the novel method, this work also applies the new method to a coercion-resistant voting system.